2022
DOI: 10.1002/prot.26332
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of the human cone‐rod homeobox transcription factor

Abstract: The cone-rod homeobox (CRX) protein is a critical K50 homeodomain transcription factor responsible for the differentiation and maintenance of photoreceptor neurons in the vertebrate retina. Mutant alleles in the human gene encoding CRX result in a variety of distinct blinding retinopathies, including retinitis pigmentosa, cone-rod dystrophy, and Leber congenital amaurosis. Despite the success of using in vitro biochemistry, animal models, and genomics approaches to study this clinically relevant transcription … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…However, a recent study reported that single CRX whole-gene deletion also causes dominant late-onset macular disease [45]; therefore, further research on this molecular mechanism is required. Mutations within the transactivation domain have no restrictions on the type of mutation due to NMD escape, but mutations that cause large changes, such as truncating mutations, appear to be necessary for most pathological changes [46]. These mutations can appear much more diverse than single-amino-acid substitutions, which may be the cause of more diverse clinical features in the mutations of the transactivation domain than in mutations of the homeodomain in our genotype-phenotype analysis.…”
Section: Discussionmentioning
confidence: 95%
“…However, a recent study reported that single CRX whole-gene deletion also causes dominant late-onset macular disease [45]; therefore, further research on this molecular mechanism is required. Mutations within the transactivation domain have no restrictions on the type of mutation due to NMD escape, but mutations that cause large changes, such as truncating mutations, appear to be necessary for most pathological changes [46]. These mutations can appear much more diverse than single-amino-acid substitutions, which may be the cause of more diverse clinical features in the mutations of the transactivation domain than in mutations of the homeodomain in our genotype-phenotype analysis.…”
Section: Discussionmentioning
confidence: 95%
“…Most CRX mutations cause the autosomal dominant form of CORD, accounting for 5-10% of all dominant forms of CORD [26,30,31]. Mutations in CRX genes cause a wide range of retinopathies, including retinitis pigmentosa, conerod dystrophy, and the dominant form of Leber congenital amaurosis, a disorder that is usually autosomal recessive [32,33].…”
Section: Crx Genementioning
confidence: 99%
“…Most CRX mutations cause the autosomal dominant form of CORD, accounting for 5-10% of all dominant forms of CORD [26,27]. Mutations in CRX genes cause a wide range of retinopathies, including retinitis pigmentosa, cone-rod dystrophy, and the dominant form of Leber congenital amaurosis, a disorder that is usually autosomal recessive [28,29].…”
Section: Crx Genementioning
confidence: 99%